The "Own" and the "Wise": Does Stigma Status Buffer or Exacerbate Social Rejection of College Students with a Mental Illness?. Issue 7 (3rd July 2017) - Markowitz, Fred E.; Engelman, Douglas J.
ABSTRACT: Applying Goffman's stigma-status framework and using data from a survey administered to college students (N = 556), we find that respondents who have been diagnosed with a mental illness (the "own") or who know a family member or friend with a mental illness diagnosis (the "wise") express lower desired social distance from persons with a mental illness than other respondents ("normals"). Also, informally labeling symptoms as "mental illness" reduced social distance among those similarly diagnosed. However, perceived dangerousness did not vary across stigma status, and the socially-distancing effects of perceived dangerousness were more pronounced among the "own."